The System of Electronic Adoption of Decisions of Local Government Bodies Has Been Established - Dadajonov Abdumutalib Karimovich (Zien Journals, 2021)
According to the decision of the Cabinet of Ministers of the Republic of Uzbekistan dated June 22, 2021 "on measures for the introduction of the electronic system "E-decision" to the activities of local government bodies" No 390 "is introduced electronic system, the development, agreement, acceptance, registration, and announcement of decisions and orders of local government bodies only through this system".
Keywords: electronic system; rule of law; activity; transparency